The Impact of General Elections on Stock Market Volatility in Indonesia (2004–2023) - Hamdani, Hamdani; Elvaretta , Katrina Lavenia; Wardani , Marshela Alya Kusuma; Kartiasih, Fitri (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2024)
Elections are events that play an important role in the economic aspects of a country. Elections create uncertainty and potentially affect investor sentiment, causing fluctuations in Indonesian stock prices. A few months before the election, stock prices in Indonesia showed a significant increase in the Indonesia Composite Stock Price Index (IHSG). This occurs due to an increase in purchasing power for campaign needs and an increase in the government budget. The ARCH/GARCH model is a relevant analysis instrument in looking at market volatility. This study forecasts the close value of IHSG in the election year 2024 and analyzes the effect of elections on stock price volatility in Indonesia. This research resulted in the best model is GARCH (1,1) with RMSE 604.74, MAE 484.27, and MAPE 13.37. The forecasting results from November 23, 2023 - February 29, 2023 tend to increase, the average increase is 0.097%, the biggest increase from the end of November to the beginning of the first week of December 2023 by 0.229%. The relationship between IHSG value and political month is positive. The regression equation shows the IHSG value in months containing political events is 743,53 greater than in non-political months.